Lean Manufacturing Production Management Model focused on Worker Empowerment aimed at increasing Production Efficiency in the textile sector - Sosa-Perez, V. (2020)
For companies operating within the garment manufacturing industry, having frequent downtimes in their production flows is an extremely common issue. In this context, a balanced production line is required to prevent high waiting times due to limited productive capacity. A well-balanced assembly line allows products to be produced in an optimum time while using less resources, such as machines, materials, or labour, since the right number of products is produced with the exact amount of resources, thus generating savings in production costs. This paper seeks to foster optimum resource allocation through the line balancing tool. Finally, to define a work methodology, best practices were selected, and a procedures manual was developed focusing on Standardization. Both tools were implemented after implementing changes to the company culture by means of the Employee Empowerment tool. As a result of this implementation, workers acquired greater accountability and control over the resources, methods, and equipment of their work areas. After the proposed improvements had been deployed, the company reported an increase of over 20% in production line quality, performance, and efficiency.